2009
DOI: 10.2139/ssrn.1412874
|View full text |Cite
|
Sign up to set email alerts
|

People’s Participation in Health Services: A Study of Bangladesh’s Rural Health Complex

Abstract: All rights reserved. Text and graphics may be reproduced in whole or in part and in any form for educational or non-profit purposes, provided that credit is given to the source. Reproductions for commercial purposes are forbidden. The Bangladesh Development Research Center (BDRC) disseminates the findings of work in progress to encourage the exchange of ideas about development issues in Bangladesh. Our main objective is to disseminate findings and ideas quickly, so we compromise to some degree on quality. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Rushender 7 The study result showed that about (83.8%) of the total respondent visited the UHC for seeking health care but another study showed only (34.1%) of the total respondents visited UHC for seeking health care, this indicated improvement of situation. 8 Purpose of visit showed highest number of respondents (16.2%) visited UHC for diarrheal treatment and ANC. Next (11.2%) was visited for family planning and vaccination (TT).…”
Section: Discussionmentioning
confidence: 98%
“…Rushender 7 The study result showed that about (83.8%) of the total respondent visited the UHC for seeking health care but another study showed only (34.1%) of the total respondents visited UHC for seeking health care, this indicated improvement of situation. 8 Purpose of visit showed highest number of respondents (16.2%) visited UHC for diarrheal treatment and ANC. Next (11.2%) was visited for family planning and vaccination (TT).…”
Section: Discussionmentioning
confidence: 98%
“…As a result, the coverage of institutional delivery might be less appealing than home delivery. The availability of female doctors in health facilities ensuring comprehensive maternal healthcare should be considered an apparent technical significance [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48], which might influence the optimum utilisation of maternal healthcare services in the country [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, unfriendly provider attitudes negatively affected women’s perception of the quality of maternity care [49]. Some studies found that respectful and attentive healthcare providers played a significant role in increasing the utilisation of maternal healthcare services at the health facility [47,48,49,50]. According to the WHO, healthcare programmes with a strong focus on respectful care are recommended to support changes in provider behaviours, clinical environments, and health systems to ensure that all women have access to respectful maternity healthcare services [51].…”
Section: Discussionmentioning
confidence: 99%
“…Background: B angladesh is a developing country of South Asia, located on the northern shore of the Bay of Bengal, covering 147,570 square km (1) . According to WHO and World Bank, about 10% people have a disability and among this percentage about 10.2 million people are adult in developing countries (2) [2].…”
Section: Introductionmentioning
confidence: 99%